The influence of social capital on entrepreneurial success among women entrepreneurs: The mediating roles of financial literacy and networking strength in Malaysia’s gig economy - Wan Chek, Wan Izzah Zahirah; Ishak, Noormaizatul Akmar; Othman , Abdul Azim; Baharin, Ahmad Tajudin; Alshamesti, Omar; Osman, Mohd Fisol (International Journal of Accounting, Finance and Business, 2025)
This study investigates how social capital contributes to entrepreneurial success through the mediating roles of financial literacy and networking strength among women entrepreneurs in Malaysia’s gig economy. Guided by the Resource-Based View (RBV) and Social Capital Theory, the study conceptualizes social relationships and financial knowledge as intangible assets that enhance business sustainability. A quantitative, cross-sectional design was employed involving 210 women entrepreneurs engaged in digital and gig-based ventures. Data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). Results reveal that social capital significantly influences financial literacy and networking strength, which subsequently drive entrepreneurial success. Both financial literacy and networking strength act as mediators, demonstrating that knowledge and relationship capabilities transform social capital into competitive advantage. The study offers theoretical and policy implications for empowering women entrepreneurs through financial education, social networking, and inclusive digital training aligned with Malaysia’s MyDigital Blueprint 2030 and Sustainable Development Goals (SDG 5 and SDG 8).